The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/hon.2438_116
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Mogamulizumab in Patients With Adult T‐cell Leukemia‐lymphoma in Japan: Interim Results of Postmarketing All‐case Surveillance

Abstract: that is uniquely farnesylated. Tipifarnib has been shown to be well tolerated and to have a 41% response rate (7 responses out of 17 patients) in patients (pts) with T-cell non-Hodgkin Lymphoma, including 4 objective responses in 8 pts with peripheral T-cell lymphoma (PTCL) (Witzig et al., 2011). Building on this prior experience, we report herein the preliminary efficacy, safety, and biomarker data from our ongoing Phase 2 study in PTCL.Methods: This Phase 2 study is a multi-institutional, single-arm, openl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The safety profile reported in this surveillance study was similar to that reported in our preliminary report 12 and in previous clinical trials. 10,11,15 IRRs, skin disorders, and infections which were collected as mandatory items were the most common ADRs, and the frequencies for the first two events were less than those reported in the clinical study of patients with relapsed ATL using the same administration schedule of mogamulizumab as used in this surveillance.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The safety profile reported in this surveillance study was similar to that reported in our preliminary report 12 and in previous clinical trials. 10,11,15 IRRs, skin disorders, and infections which were collected as mandatory items were the most common ADRs, and the frequencies for the first two events were less than those reported in the clinical study of patients with relapsed ATL using the same administration schedule of mogamulizumab as used in this surveillance.…”
Section: Discussionsupporting
confidence: 88%
“…and might be higher compared with that of HSCT not preceded by mogamulizumab, suggesting the risk of severe GVHD is increased by administering mogamulizumab before allogeneic HSCT in patients with ATL. 12 However, it should be paid attention to be led by a small number of patients who have many background factors. According to our multivariate analysis, poor PS of 2-4, low serum albumin <3.5 g/dL, high corrected serum calcium ≥2.75 mmol/L, and high LDH >240 IU/L were associated with poor prognosis, with P < 0.05 or of borderline significance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations